A study of semantics and morphological forms of Zulu adolescence nicknames: a case study of the inner West Townships of Durban, KwaZulu-Natal - Nzama, Thulani Blessing (My University, 2021)
Nicknames are part of the daily life of a Zulu person. They identify a person more than their given name. They influence the behaviour and personality based on the interaction and general well-being of an individual. They discipline, praise and even mock the person. The aim of the study was to present the morphology and semantics of Zulu adolescence nicknames. The study applied research design largely informed by a qualitative approach, while ethnography was the main method used for data collection. It was conducted amongst the Zulu adolescent peers in the Clermont KwaDabeka area in Durban (South Africa). The Theory of Nicknames was very useful to the semantic analysis of the Zulu adolescence nicknames since the meanings of the nicknames are not found in the dictionary definitions or even necessarily in their origins, but in their usage in everyday life. These nicknames present peculiar morphological structures, therefore, morpheme-based morphology theory was used in identifying and describing morphemes that constitute these nicknames. The study revealed that Zulu adolescence nicknames possess denotative, connotative and etymological meaning. The study concluded that nicknames hold semantic value governed by socio-cultural factors and convey messages. It also observed on the one hand that nicknames derived from nouns are derived from simple noun roots. On the other hand, compounds, verbs and diminutives are derived from complex structure. The study recommends that future research on Zulu nicknames focus on syntax or phonology
A dissertation submitted to the Faculty of Humanities, University of The Witwatersrand in partial fulfilment of the requirements of the degree of Master of Arts in African Languages and Linguistics, 2021